Poverty and Income Replacement Profile Among EPF Retiree in Malaysia - Vaghefi, Negin; Kari, Fatimah; Abdul Mutalib, Muzalwana (Springer Verlag, 2017)
Social security policies often focus on replacement rates, which indicate retirement income or social security benefits in relation to preretirement income. The higher replacement rate among the pensioners would ensure that the ageing society would have sufficient income to lead a normal life after retirement. This study examined factors that influencing the income replacement rate of Malaysian Employee Provident Fund (EPF) retirees. The analysis was based on a nationwide survey conducted in 2013–2014 among EPF retiree. A logit model was used to evaluate the likelihood of selected socio-demographic and economic factors contributing to income of the retirees. The results indicated that around 62 % of elderly has lower retirement income compared to their preretirement income and it makes them more vulnerable to unpredictable events and financial conditions. The study suggested that the income replacement rate of elderly could be strengthened by investing in ageing workforce, raising retirement age, enhancing educational achievements of low income groups and restructuring employment. These may in turn increase the availability of skilled workers, enhancing the national productivity, increase the income security of retirees, reduce poverty, and develop economic growth of the country.